THE USE OF ARTIFICIAL INTELLIGENCE IN THE RUSSO-UKRAINIAN WAR - Đorić, Marija; Glišin, Vanja (The Policy of National Security, 2023)
The Russo-Ukrainian conflict, with its geopolitical importance, goes beyond regional borders, which is why it is inevitable that we talk about it as a conflict of global proportions. The direct and/or indirect involvement of numerous countries of the world in this conflict, especially in the form of military-technical, technological, economic and economic involvement, confirms the above. The focus of our work is the military-technical aspect, i.e., the use of artificial intelligence and its importance for the present and future of warfare. In the first part of the work, artificial intelligence is conceptually defined, and then the use of artificial intelligence in the military industry is elaborated, as well as its importance in changing the conventional way of warfare. Finally, the authors deal with the use of artificial intelligence in the Ukrainian war, in order to point to a new form of arms race.
Keywords: artificial intelligence; drones; robots; Russia; Ukraine; Russo-Ukrainian conflict; geopolitics; security